Compressive strength and chloride resistant of WPSA geopolymer concrete containing RCA / Wan Muhammad Faris W. Yusoff - W. Yusoff, Wan Muhammad Faris (2015)
The production of cement used high amount of energy and release high amount of green house gases to atmosphere such as carbon dioxide (CO2) that causes an environmental problem. The use natural aggregate as an aggregate in the concrete production can cause depletion of virgin aggregate. In order to cater this problem, an alternative method needs to be studied. Geopolymer concrete is a green concrete material that produces by using pozzolanic material without the presence of cement. This concrete material was generated by the geopolymerization process between Silicon (Si) and Aluminium (Al) element in the source material with the alkaline activator. This research is focusing on the production of the geopolymer concrete using waste paper sludge ash (WPSA ) as the main binder and the recycle concrete aggregate (RCA) as the aggregate. The compressive strength and the chloride permeability were studied in order to determine the potential of these materials in geopolymer. The combination of sodium hydroxide solution and sodium silicate solution were used to activate the Si and Al element in the WPSA material. The aggregates replacement level of 25%, 50%, 75% and 100% of RCA in the geopolymer concrete mixture were used. The concrete samples of size 100mm x 100mm x 100mm cube and 100mm (dia.) x 50mm was casted. The WPSA geopolymer concrete specimens were cured in the oven for 24 hour at 60°C temperature before being cured at ambient condition until the age for testing. The geopolymer concrete were tested their compressive strength at 3, 7, 28, 56 and 90 days of ages. Meanwhile, the rapid chloride permeability test (RCPT) was used to determine the chloride penetration of WPSA geopolymer concrete at the age of 7 and 28 day. The compressive strength and permeability of chloride of the WPSA geopolymer concrete specimens was analyzed. It is concluded that the WPSA geopolymer concrete exhibit a lower compressive strength compared to the geopolymer concrete that using low calcium pozzolanic material such as fly ash and slag. The RCPT test value shows that WPSA geopolymer concrete was high permeable to the chloride. Based on the finding, WPSA geopolymer concrete can be categorized as a low strength concrete hence it can be utilized as a non-structural material for construction purposes.